CASP4 gene silencing in epithelial cancer cells leads to impairment of cell migration, cell-matrix adhesion and tissue invasion. Issue 1 (December 2018) - Papoff, Giuliana; Presutti, Dario; Lalli, Cristiana; Bolasco, Giulia; Santini, Simonetta; Manelfi, Candida; Fustaino, Valentina; Alemà, Stefano; Ruberti, Giovina
Abstract Inflammatory caspases, including human caspase-4 (CASP4), play key roles in innate immune responses to promote fusion of phagosomes harboring pathogenic bacteria with lysosomes, halt intracellular replication of pathogens, maturation and secretion of pro-inflammatory cytokines. The role of inflammatory caspases in cancer cells remains poorly investigated. Here, we explored the consequences of modulatingCASP4 expression levels on the migratory behavior of epithelial cancer cell lines. By a gene silencing approach andin vitro andin vivo studies we show that down-regulation of CASP4 leads to impaired cell migration and cell-matrix adhesion. This phenotype is accompanied by an increased actin cytoskeleton polymerization, changes in the overall organization of adherens junctions (AJs) and number and size of focal adhesions. Interestingly, the cell migration deficit could be reversed by epithelial growth factor treatment, and depletion of calcium ions unveiled a role of CASP4 in the novo assembly of AJs, suggesting that the role of CASP4 is not cell-autonomous. Finally, CASP4 -silenced A431 cells exhibited a severe reduction in their ability to invade lung tissue, when injected into nude mice. Overall, our data support the emerging evidence that inflammatory caspases can regulate cell migration through actin remodeling and uncover a novel role of CASP4 in cancer cell behavior.